Providing Benefits Of Protection Intellectual Property Of Products In UMKM Traditional Jamu - Murniati, Wahyuning (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
UMKM Jamu is engaged in the health sector by producing traditional herbal medicine which is believed to be effective in preventing the growth of cancer cells and various other diseases. This UMKM is located in Wonorejo Village, Lumajang Regency and from the beginning, marketing was only done in the area around Lumajang. Over time, UMKM managers must think about product protection. Therefore, this assistance is carried out with the aim of being able to provide understanding to the UMKM Jamu Ibuk producers related to Intellectual Property and its benefits for UMKM. In its activities, it was explained that product protection would increase originality, so of course it would increase sales. In addition, product protection will prevent producers from various parties who want to make plagiarism from Jamu Ibuk.